Constructing Sulfonic Acid Functionalized Anthracene Derived Conjugated Porous Organic Polymer for Efficient Metal‐Free Catalytic Acetalization of Bio‐Glycerol. Issue 17 (13th June 2017) - Kundu, Sudipta K.; Singuru, Ramana; Hayashi, Taku; Hijikata, Yuh; Irle, Stephan; Mondal, John
Abstract: Sulfonic acid (‐SO3 H) functionalized anthracene derived conjugated porous organic polymer (AnPOP‐SO3 H) have been constructed through Friedel‐Crafts alkylation of anthracene by using formaldehyde dimethyl acetal as a cross‐linker and anhydrous FeCl3 as a promoter followed by sulfonation of aromatic rings using chlorosulfonic acid under controlled reaction conditions. Morphological evolution, porous structure, nature and strength of the acid sites and structural integrity with different chemical environments have been comprehensively examined by employing HR‐TEM (High Resolution Transmission Electron Microscopy), FE‐SEM (Field Emission‐Scanning Electron Microscopy), Powder X‐ray diffraction, N2 sorption, NH3 ‐TPD (Temperature Programmed Desorption), solid state 13 C CP MAS‐NMR (Cross Polarization Magic Angle Spinning‐Nuclear Magnetic Resonance), HAADF‐STEM (High Angle Annular Dark Field‐Scanning Transmission Electron Microscopy) with the corresponding elemental mapping and FT‐IR (Fourier Transform Infrared) spectroscopic tools. This newly designed AnPOP‐SO3 H metal‐free organocatalyst exhibited an excellent catalytic activity in the acetalization of Bio‐Glycerol with acetone, furfural, and benzaldehyde under solvent free and ambient temperature conditions to furnish 2, 2‐dimethyl‐1, 3‐dioxalane‐4‐methanol (solketal) derivatives, with quantitative conversion and good selectivities. An enhancement in the catalytic performance of the nanohybrid metal‐free solid acid catalyst is observed compared with the conventional reported catalysts which could be attributed to the presence of high acidic sites, huge surface area accompanied with the highly rigid cross linked framework thereby facilitating easy diffusion of organic substrates to interact with the catalytic active sites and prohibiting water diffusion inside the pore owing to the hydrophobic nature of the catalyst. The investigated AnPOP‐SO3 H represents a novel class of promising heterogeneous metal‐free organocatalyst with ten recycles in succession and no sign of catalyst deactivation, useful for the transformation of Bio‐Glycerol to value‐added chemicals in an eco‐friendly manner for future industry. Abstract : Sulfonic acid functionalized highly cross‐linked Anthracene derived Porous Organic Polymer (AnPOP‐SO3 H) has been developed though Friedel‐Crafts alkylation of anthracene by using formaldehyde dimethyl acetal as a cross‐linker and anhydrous FeCl3 as a promoter followed by sulfonation of aromatic rings using chlorosulfonic acid under controlled reaction conditions which exhibits excellent catalytic performance with superior stability in metal‐free catalytic acetalization of Bio‐Glycerol.